The social work skills workbook 8e - Cournoyer, Barry. (Cengage Learning, 2017)
Eighth Edition, enables you to develop proficiency in professionalism and the essential social work skills. After introducing 10 dimensions of professionalism, the book offers multiple opportunities to rehearse, practice, and self-assess social work skills needed in a contemporary practice -- helping you become a more confident, ethical, and effective helper. Each social work skill supports one or more of the 43 knowledge and value statements and the 31 practice behaviors that elaborate core competencies in the 2015 Educational Policy and Accreditation Standards (EPAS) of the Council on Social Work Education (CSWE). The skills also align with nationally standardized licensing exams. The text includes explanations grounded in contemporary research, assessment tools and processes, and experiential components that help you get a realistic sense of the field. Case examples and skill-building exercises cultivate your professionalism and expertise.